IMPROVING EMPLOYEE SELF-DETERMINATION BY ANALYZING INDIVIDUAL DIFFERENCES (The Indonesian Journal of Business Administration, 2019)
English Prestasi Learning Center or EPLC is one of the non-formal educational institutions engaged in English language courses that was founded in 2013. Since EPLC adopted the learning methods from Kampung Iggris, Pare, Kediri which had further developed rapidly so that they want to expand the business. In this research, the low dimension of self-interest in the ethical climate is related to differences in motivation of each individual working at EPLC and then becomes the basis for the authors to analyze more deeply by using the Theory of Basic Human Needs by Abraham Maslow (1954) and The Theory of Basic Values by Schwartz (2005). These two theories underlie individual differences which basically come from different backgrounds, visions and behaviors which are then supported by their own motivation to act. From the results of these individual differences interviews, information is obtained that individual differences that cause individuals in EPLC are less able to determine their own choices which then refers to the Theory of Self-Determination Proposed by Deci & Ryan (2008). These three theories are then put together and then compared to get information which dimensions need to be improved. From the root of the problem, the authors provide recommendations in this study namely, conduct training, conduct management planning, form human resource divisions, make key performance indicator, and apply performance appraisal at EPLC. With these recommendations, it is expected that EPLC can help improve motivation for employees, so that they can contribute more to the development of EPLC.Keywords: Ethical Climate, Self-Determination, Individual Differences, Self-Interest, EPLC